2019
DOI: 10.19044/esj.2019.v15n25p358
|View full text |Cite
|
Sign up to set email alerts
|

Excange Rate Fluctuation and Real Sector Performance in Nigeria: A Disaggregated Analysis

Abstract: The Nigerian real sector is facing serious challenges due to exchange rate volatility. All the past efforts of the Central Bank of Nigeria to make naira have high international competitiveness had not yielded much result. In view of this, this study investigates the relationship between exchange rate fluctuation and the performance of the real sector in Nigeria while looking at disaggregated components of agricultural, industrial, building and construction, wholesale and retail trade, and services with a scope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Several cross-country and country-specific studies have been conducted to examine the impact of exchange rate movement on macroeconomic performance: national output (Ojo & Alege, 2014), output growth (Adeniran et al, 2014;Oladapo & Oloyede, 2014;Okorontah & Odoemena, 2016;Ismaila, 2016), industrial output growth (Usman and Adejare; 2012), sectoral output performance (Falana, 2019), domestic private investment (Bakare, 2011), foreign reserves (Khan, 2013), among others. The results of these studies are conflicting; while some showed a positive relationship, others revealed a negative effect of exchange rates while others showed that exchange rates have no effect.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…Several cross-country and country-specific studies have been conducted to examine the impact of exchange rate movement on macroeconomic performance: national output (Ojo & Alege, 2014), output growth (Adeniran et al, 2014;Oladapo & Oloyede, 2014;Okorontah & Odoemena, 2016;Ismaila, 2016), industrial output growth (Usman and Adejare; 2012), sectoral output performance (Falana, 2019), domestic private investment (Bakare, 2011), foreign reserves (Khan, 2013), among others. The results of these studies are conflicting; while some showed a positive relationship, others revealed a negative effect of exchange rates while others showed that exchange rates have no effect.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%